Pengaruh Bullying Terhadap Self Esteem Pada Siswa MTS Al-Jam’iyatul Washliyah Pematang Johar Medan - Sartika, Neti; Rismawati Munthe (Universitas Negeri Medan, 2025)
The phenomenon of bullying in schools, such as exclusion and physical/verbal violence, has become a serious problem affecting adolescent development. An unsafe environment significantly threatens students' self-esteem, causing low self-confidence. This study aims to examine the effect of bullying on self-esteem in students. This study uses a quantitative method, with an ex-post facto type. The study was conducted at MTS AL-JAM'IYATUL WASHLIYAH PEMATANG JOHAR Jl. Johar Raya, Tj. Selamat, Percut Sei Tuan District, Medan City, North Sumatra 20371. The research time was June 2025. The population was 15 students. The sampling method was total sampling technique. Data collection used a questionnaire. The results of the study showed that there was a very significant influence between bullying and self-esteem, the correlation value R = 0.993 and a significance value <0.000. indicating that the higher the intensity of bullying experienced, the greater the influence on the level of individual self-esteem. The validity test of 15 student respondents with a significance of 5% of the bullying variable showed 27 spread across 3 aspects, namely 22 valid and reliable